Weatherability Temperature Field and Temperature Stress Simulation of Inorganic Mortar Compound Panel with Insulation and Decoration Based on Actual Engineering Model. (September 2019) - Xiang-Lei, Hu; Lin, Wang
Abstract: Finite element simulation software can explore the heat transfer and deformation of complex shapes and can be used as an auxiliary tool for large weathering tests. Based on the results by ANSYS software, this paper explored temperature field and temperature stress field of inorganic mortar compound panel with insulation and decoration (IMCP), considering weather resistance experiment based on practical engineering. The paper holds that the relevant regulations should provide the mortar adhesion area reinforcement of IMCP may be not less than 80%. Moreover, in order to adapt to the temperature deformation, the width of the joint of IMCP should also be specified and recommended not be less than 5 mm.